System and key to genera of the family Sapindaceae Juss. in Vietnam - Tam, Ha Minh; Khoi, Nguyen Khac; Phuong, Vu Xuan (Academia Journal of Biology, 2015)
The family Sapindaceae Juss. is widespread in Vietnam with 25 genera. Although the family is important, so far in Vietnam, there was not a full taxonomy system and a key to genera of this family. We have based on the Radlkofer system (1932), Muller & Leenhouts’ supplement (1976) and Takhtajan’s supplement (1996) to divide this family in Vietnam into 2 subfamilies, 10 tribus and 25 genera. We have agreed with the combination of the tribu Aphanieae in the tribu Lepisantheae by Muller & Leenhouts (1976) and Takhtajan (1996) and so combined the genera Aphania, Erioglossum, Otophora in the genus Lepisanthes. All after, we have constructed the key to 25 genera in Vietnam basing on the vegetative, flower and fruit characters.